Pengaruh Latihan Treadmill Dan Cycle ErgometryTerhadap Vo2 Max - Dewi, Isnaini Kusuma, Totok Budi Santoso, S.Fis., SPd., MPH (2016)
Background : VO2max is very important. But today there are many people who do not understand about VO2max. VO2max is the ability of the heart, lungs and blood vessels to function optimally in a state of rest and exercise to take in oxygen and distribute to network active for the metabolism of the body. Purpose : To determine the effect of exercise on the treadmill and cycle ergometry VO2max. Method : This study is a pre experimental with one group pre-test and post-test design, the sample given a treadmill and cycle exercise ergometrty for 4 weeks with a frequency of 3 times a week, intensity 60-70% of maximum heart rate. Measurement of VO2max dilakuakan with MFT. analyse data using Wilcoxon test to test the effect. Result : There was an effect of exercise treadmill and cycle ergometry against VO2max, after the performed statistical tests obtained using Wilcoxon test p-value of 0.005 Conclusion: There are the exercise treadmill and cycle ergometry the VO2max.